Active gaming and self-paced exercise: A self-determination perspective - Wadsworth, D. D.; Daly, C. M.; Foote, S. J. (Journal of Sports Medicine and Therapy, 2018)
Purpose: This study aimed to identify physical activity, enjoyment, and factors for future activity between an active video game (AVG) condition and self-paced exercise (SPE) among college-aged students.